From Traditional Trade to E-Commerce: Case Analysis on Empowerment of Conventional Market Traders in Yogyakarta - Muslim, Aziz (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2023)
Conventional markets have increasingly marginalized in the modernization era from consumers, particularly during the COVID-19 pandemic, and have affected the decreasing traders' income. Therefore, this study aims to analyze the efforts to empower conventional market traders in increasing their income through the development of an e-commerce transaction system. A qualitative approach was used with data collection techniques, such as interviews and observations, while the data were analyzed by interactive technique. According to the results, the development of an e-commerce transaction system in conventional markets was conducted with a strategy of assessing market potential, socializing e-commerce concepts, and training on website management. At the implementation level, two factors behind the success of this program were the role of universities and financial support from the local government. Furthermore, the inhibiting factors include the social motivation of consumers in shopping and the cost of shipping goods. The efforts to develop an e-commerce transaction system was ineffective in increasing traders' income, while the loyalty of consumers who continue to shop at the market can contribute to the increase in income.